Code Switching Preferences and Necessities in EFL Learners : A Literature Review - Harnef Uyat Sentomoy (Universitas Nusantara PGRI Kediri, 2024)
This study examines why EFL learners in Indonesia often switch between their English to native language when talking, primarily their reasons to do so whether itsnecessities or preferences. The research method is done through a systematic literature review from numerous previous studies of journal and thesis that are found in Google Scholar using search engine Publish or Perish 8.The results obtained are fascinatingly diverse from their own reasons to their environment, for example habits, shyness, and following today’s social trends.The findings emphasize the complexity of EFL learners' code-switching. This article aims to provide valuable insights into the linguistic phenomenon of Code-Switching. This information is intended to be useful for both language educators and learners alike, and has suggestions such as Vocabulary Enchancement Strategies, Awareness and Education etc.